Dramatic improvement of segmental Zoster Paresis by late-onset antiviral therapy - Onder, Halil; Celik, Gokcen (Nepal Journal of Neuroscience, 2021)
Focal paresis secondary to Herpes zoster (HZ) is a rare neurological complication and should be kept in mind in the differential diagnosis of acute weakness with corresponding dermatomal rashes. In this case report, we illustrate an 84-year-old male patient, who presented with focal upper extremity weakness following HZ on right C4-8 dermatome. After clinical and electrophysiological evaluations, segmental zoster paresis was diagnosed. Although antiviral medication(oral brivudine) had been administered previously, oral valacyclovir and low dosage methylprednisolone were initiated. In the following 2 months interval, a progressive and dramatic recovery in extremity weakness and neuropathic pain were achieved. The clinical course of this patient may give substantial perspectives regarding the clinical evaluation of similar cases.